2020
DOI: 10.1080/23311983.2020.1748987
|View full text |Cite
|
Sign up to set email alerts
|

Reading visual design of outdoor signs in Kuta (A case study of multimodal linguistic landscapes)

Abstract: This is a case study of linguistic landscapes (LL) with multimodal approach, which aimed at analysing the visual grammar of commercial outdoor sign. LL is a study of signs in public space. These signs include all traffic signs, billboards, site names, and advertisements. Multimodal approach is a new concept of analysis that analyses signs from three aspects, and it is representation, interaction and composition. The data in this study is classified as a secondary data that randomly chosen from author previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
2
9
0
1
Order By: Relevance
“…This change in situation impacts the use of the international language of English, especially on commercial outdoor signs. This phenomenon is also seen in another study where commercial designs in Kuta use English and foreign languages in their advertisements (Mulyawan, 2020) . On the other hand, the LL situation in Bali, especially in the Kuta area, has become a concern for language and cultural observers concerned that the dominance of foreign languages over Balinese in the Kuta area will affect the local identity of the community.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…This change in situation impacts the use of the international language of English, especially on commercial outdoor signs. This phenomenon is also seen in another study where commercial designs in Kuta use English and foreign languages in their advertisements (Mulyawan, 2020) . On the other hand, the LL situation in Bali, especially in the Kuta area, has become a concern for language and cultural observers concerned that the dominance of foreign languages over Balinese in the Kuta area will affect the local identity of the community.…”
Section: Introductionsupporting
confidence: 54%
“…Previous studies found that English dominates the linguistics landscape (LL), such as Kuta (Mulyawan, 2020;Mulyawan & Ratna Erawawti, 2019), in Ubud (Ariani & Artawa, 2021;Mulyawan, 2019) and Bali as a whole (Khazanah & Kusumaningputri, 2021;Wulansari, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The informative function of the digital linguistic landscape includes information delivering function, information indicating function, and information mediation function. The information delivering function is manifested in the form of linguistic information at an intuitive level [ 85 ]; the information indicating function is manifested in the form of multimodal linguistic landscapes that serve as an aid to comprehension or emphasis [ 86 ]; and the information mediation function is manifested in the form of short, guiding messages that point to a broader pool of relevant information resources [ 74 ]. The symbolic function of digital linguistic landscape refers to its ability to reflect market trends and current social conditions [ 87 , 88 ], as the information of digital linguistic landscape is shared, convenient, and expandable to facilitate the wide dissemination of social phenomena [ 89 ], and its information most directly reflects often the most cutting-edge social hotspots and trends.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research has been around since 1978, but has only been highlighted since the research conducted by on linguistic landscapes. And this research is what underlies research on linguistic landscapes that are better known and developed today (Mulyawan, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Non-commercial signs are signs made by the government or certain agencies with the aim of providing information about something without any purpose for the benefit of seeking profit or profit. The commercial sign is a sign made by individuals or companies to attract readers with the aim or orientation of profit or profit (Mulyawan, 2020). The symbolic function in landscape linguistic studies is the emergence of a feeling of the use of certain language signs by a group of people.…”
Section: Introductionmentioning
confidence: 99%